2015
DOI: 10.3109/17453674.2015.1037222
|View full text |Cite
|
Sign up to set email alerts
|

Medial percutaneous hemi-epiphysiodesis improves the valgus tilt of the femoral head in developmental dysplasia of the hip (DDH) type-II avascular necrosis

Abstract: Background and purpose Avascular necrosis (AVN) is a major cause of disability after treatment of developmental dysplasia of the hip (DDH), leading to femoral head deformity, acetabular dysplasia, and osteoarthritis in adult life. Type-II AVN is characterized by retarded growth in the lateral aspect of the physis or by premature lateral fusion, which produces a valgus deformity of the head on the neck of the femur. We investigated the effect of medial percutaneous hemi-epiphysiodesis as a novel technique in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…Later, other studies have shown improved radiological outcomes using the guided growth method. [11][12][13][14] This study is the first to compare guided growth with corrective osteotomy for this particular hip condition. The literature on the management of valgus deformity due to AVN comprises patients already treated by different procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Later, other studies have shown improved radiological outcomes using the guided growth method. [11][12][13][14] This study is the first to compare guided growth with corrective osteotomy for this particular hip condition. The literature on the management of valgus deformity due to AVN comprises patients already treated by different procedures.…”
Section: Discussionmentioning
confidence: 99%
“…14 Previous studies have outlined correction of the caput valgum deformity with a substantial decrease in the HSA after guided growth. [11][12][13][14] As for the neck geometry, Peng et al 14 found no significant difference in the NSA at two years postoperatively. In our study, there was a significant decrease in both HSA and NSA in the guided growth group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An improvement in physeal inclination was demonstrated with growth. 64 The age at surgical intervention depended upon the age of diagnosis of the lateral proximal femoral growth abnormality, which may not occur in hip dysplasia patients until later in childhood.…”
Section: Guided Growth At the Hipmentioning
confidence: 99%